Networking in management of relationships with the sports and leisure service market - Widawska-Stanisz, Agnieszka (Quality in Sport, 2018)
The aim of the paper is to present the opportunities provided by the network of contacts and recommendations in business relationship management. The starting point of the present study is relationship marketing which assumes that relationships can be built, sustained and enriched not only with buyers of products and services but also with other entities from the enterprise market environment. The sports and leisure service market is a very specific sector and, at the same time, a huge industry. In the paper, there are presented the assumptions of the marketing of relationships, recommendations and networking activities - the most important from the point of view of building relationships. The text is supplemented with the assumptions of the relationship marketing model of the sports and leisure company taking into account the use of business networks with, among others, the entities such as dietician services, diet catering companies, companies providing sportswear and supplements.